Early intervention in psychiatric disorders across cultures - Chen, Eric Yu-hai; Ventriglio, Antonio; Bhugra, Dinesh (Oxford : Oxford University Press, 2019)
Evidence indicates a correlation between early intervention and improved response in psychiatric disorders. Yet the majority of evidence is from high-income countries, and there is a lack of evidence and resources on the impact of early intervention across cultures and in low- and middle-income countries. Early Intervention in Psychiatric Disorders across Cultures aims to bridge this gap by focusing on the evidence and methods of intervention in less affluent countries. It covers mood disorders, personality disorders, addictions, and other psychiatric conditions, whilst most research has focused on psychoses and bipolar disorder. Over 17 chapters, this resource guides the reader through an array of approaches to early intervention, from brain imaging and available care pathways, to cultural and societal factors. Part of the Oxford Cultural Psychiatry series, this resource offers readers a picture of the current health care pathways available as well as social, cultural, and ethical considerations to apply in practice--from publisher's website.
Introduction / Eric Y.H. Chen, Antonio Ventriglio, and Dinesh Bhugra -- Early interventions to prevent stigmatization and its consequences / Norman Sartorius -- Role of culture in early interventions / Antonio Ventriglio and Dinesh Bhugra -- Brain changes in the early course of schizophrenia / Matcheri S. Keshavan, Paulo Lizano, and Jaya Padmanabhan -- Brain changes in psychosis: Understanding their significance as the basis for better prevention / Peter Falkai, Andrea Schmitt, Moritz Rossner, Thomas Schulze, and Nikolaos Koutsouleris -- Detecting the first signs of emergining psychosis / Frauke Schultze-Lutter -- Are ethnic differences in pathways to care for psychosis in England reducing? Analysis of two population-based studies of first-episode psychosis in South London / Sherifat Oduola, Craig Morgan, and Tom K.J. Craig -- Early intervention for psyhosis: perspective after 15 years of development / Eric Y.H. Chen, Sherry Kit-wa Chan, Wing-Chung Chang, Christy Lai-ming Hui, Edwin Ho-ming Lee, tak-Lam Lo, Catherine Shiu-yin Chong, Wai-song Yeung, Roger Man-kin Kg, Eric Fuk-chi Cheung, Dicky Wai-sau Chung, and Lap-tak Poon -- Experiences and lessons from the Singapore early pcyhosis intervention programme / Swapna K. Verma, Poon Lye Yin, Helen Lee, and Chong Siow Ann -- Early psychosis initiative in Japan: challenges and opportunities / Masafumi Mizuno, Naomi Inoue, Takahiro Nemoto, Naohisa Tsujino, Naoyuki Katagiri, and Tomoyuki Funatogawa -- Family involvement in first-episode psyhosis: The Indian scenario / Greeshma Mohan, R. Padmavati, and R. Thara -- From principles to practice: Translating the philosophy of early intervention to individuals with emerging bipolar disorders / Jan Scott -- Early intervention in bipolar disorders: setting the the stage from mechanisms to models / Gin S. Malhi, Grace Morris, Amber Hamilton, and Tim Outherd -- Early intervention in personality disorders / John M. Oldham -- Early detection and timely intervention for borderline personality disorder / Andrew Chanen -- Early intervention in underage drinking; preliminary results in Brazil / Arthur Guerrra de Andrade, erica Rosanna Siu, Carla Dalbosco, Telma Tiemi Schwindt Diniz Gomes, and Paulina do Carmo Arruda Viera Duarte -- Where next for early intevention programmes? / Dinesh Bhugra, Antonio Ventriglio and Eric Y.H. Chen.
Online resource; title from PDF title page (EBSCO, viewed May 13, 2019)
Includes bibliographical references and index
eBooks on EBSCOhost
Keywords: Mental illness -- Treatment; Mental health services -- Cross-cultural studies; Cross-cultural studies; Mental Disorders -- therapy; Mental Disorders -- prevention & control; Early Diagnosis; Early Medical Intervention; Cross-Cultural Comparison; Maladies mentales -- Traitement; Services de santé mentale -- Études transculturelles; Études transculturelles; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Cross-cultural studies; Mental illness -- Treatment; Mental health services; Electronic books; Cross-cultural studies